Association of fatty acid ethyl esters in meconium with behavior during childhood. (1st January 2021) - Singer, Lynn T.; Min, Meeyoung O.; Momotaz, Hasina; Powers, Gregory; Minnes, Sonia; Bearer, Cynthia F.
Highlights: Prenatal alcohol exposure (PAE) can result in child behavioral impairments. Early diagnosis of PAE for intervention is impeded by lack of valid assessments. Fatty acid ethyl esters (FAEE) in meconium related to behavior of children with PAE Higher concentrations of FAEEs predicted higher aggressive/delinquent behavior. FAEEs in meconium may be markers for aggressive/delinquent behavior related to PAE. Abstract: Objective: To examine associations between amounts of fatty acid ethyl esters (FAEEs) in meconium and behavior in school aged children exposed to alcohol and drugs in utero. Methods: A secondary analysis of a prospective cohort of cocaine, polydrug exposed children, primarily African-American, low socioeconomic status, recruited at birth into a longitudinal study. FAEEs were quantified with gas chromatography via a flame ionization detector. Meconium was analyzed for FAEEs for 216 newborns of whom 194 were assessed with the Child Behavior Checklist (CBCL) at ages 4, 6, 9, 10, 11, and 12. Generalized estimating equation analyses were used to assess the relationship of quantity of FAEEs to outcomes, controlling for maternal psychological distress. Results: Higher concentrations of FAEEs (ethyl myristate, ethyl palmitate, ethyl oleate, ethyl linoleate, and ethyl linolenate) were associated with caregiver reported aggressive and/or delinquent behavior at ages 10 and 12. After control for caregiver psychological distress, and age, significant (p < 0.05) FAEE by age interactions were found for ethyl myristate for aggression and for ethyl oleate, ethyl linoleate and ethyl linolenate for delinquency. Thus, higher concentrations of FAEE were related to more caregiver reported aggressive and delinquent behaviors of clinical significance at ages 10 and 12. Conclusion: Higher concentrations of FAEEs in meconium are potential markers for children at risk for aggressive and delinquent behaviors related to the effects of prenatal alcohol exposure.